2009
DOI: 10.1158/1055-9965.epi-08-0905
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusand Squamous Cell Carcinoma of the Skin

Abstract: Squamous cell carcinoma (SCC) of the skin is a tumor with greatly increased incidence among immunosuppressed patients; therefore, an infectious cause of SCC has long been sought. We performed a hospital-based case-control study of Staphylococcus aureus and biopsies of SCC (n = 82), basal cell carcinoma (n = 142), actinic keratosis (n = 57), and seborrhoeic keratosis (n = 72) in comparison with biopsies from healthy skin of these 353 immunocompetent patients. In a S. aureusspecific PCR, targeting the nuc gene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 41 publications
6
76
1
8
Order By: Relevance
“…The prevalence of S. aureus has been reported to be higher in skin SCC than in BCC or normal skin (Kullander et al , 2009). In our cohort, S. aureus DNA was detected in over 30% of invasive SCC and SCC in situ and, less frequently, in BCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of S. aureus has been reported to be higher in skin SCC than in BCC or normal skin (Kullander et al , 2009). In our cohort, S. aureus DNA was detected in over 30% of invasive SCC and SCC in situ and, less frequently, in BCC.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus was detected by PCR amplification of the S. aureus nuc gene using previously published primers, forward 5′-GCGATTGATGGTGATACGGTT-3′ and reverse 5′-AGCCAAGCCTTGACGAACTAAAGC-3′, resulting in a 263-bp product (Brakstad et al , 1992; Kullander et al , 2009). PCR products were further analysed by DNA sequencing to confirm the nuc gene sequence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria have been linked to cancer by two mechanisms: induction of chronic inflammation and production of carcinogenesis. The staphylococcal α-toxin has been shown to activate both several cytokines which have been linked to all steps in tumor development and nuclear factor κB, known tumor promoter in the development of hepatocellular carcinoma (Kullander et al, 2009). …”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The transcriptional results of fnbpA and fnbpB indicated that PGE 2 can in part regulate the transcription of genes coding for fibronectin-binding proteins.Several observations supported that S . aureus colonization is significantly higher in some cancer patients than that in the healthy [6264] and COX-2 appears as frequently upregulated in tumor cells [65,66]. Take the Cutaneous T-cell lymphomas (CTCL) as an example, COX-2 expression has recently been proven in CTCL cells, and treatment with the selective COX-2 inhibitor celecoxib resulted in decreased cell growth and viability [66].…”
Section: Discussionmentioning
confidence: 99%